2015
DOI: 10.1021/jacs.5b08048
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Dynamics of Receptor Proteins in a Plasma Membrane

Abstract: The interactions of membrane proteins are influenced by their lipid environment, with key lipid species able to regulate membrane protein function. Advances in high resolution microscopy can reveal the organisation and dynamics of proteins and lipids within living cells at resolutions < 200 nm. Parallel advances in molecular simulations provide near-atomic resolution models of the dynamics of the organisation of membranes of in vivo like complexity. We explore the dynamics of proteins and lipids in crowded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(163 citation statements)
references
References 74 publications
5
157
1
Order By: Relevance
“…Their results showed that the extent of peptide solvation within bicelles and nanodiscs is strongly dependent upon location of the peptide within the membrane mimetic environment and that dynamics of membrane mimetics can be rather different when proteins are embedded compared to the protein-free environment. This observation is in agreement with other molecular dynamics simulations studies, which have also revealed the complex interplay between proteins and lipids 52,53 .…”
Section: Opportunity For Use In Molecular Simulationsupporting
confidence: 93%
“…Their results showed that the extent of peptide solvation within bicelles and nanodiscs is strongly dependent upon location of the peptide within the membrane mimetic environment and that dynamics of membrane mimetics can be rather different when proteins are embedded compared to the protein-free environment. This observation is in agreement with other molecular dynamics simulations studies, which have also revealed the complex interplay between proteins and lipids 52,53 .…”
Section: Opportunity For Use In Molecular Simulationsupporting
confidence: 93%
“…By its very nature CG models may not be suited to the study of ligand binding in highly specific pockets where packing of ligand and protein is tight. However, as described above, binding of lipid molecules to membrane protein surfaces is generally less structurally specific than binding at a typical ligand binding site [14], and the CG approach has been used to study lipid-protein interactions at annular (boundary) lipid binding sites for a wide range of lipid molecules, including cholesterol [11,[25][26][27][28][29][30]. Hydrogen bonds are not modelled explicitly in most force fields used in molecular dynamic simulations, and in the Martini force fields used in CG simulations are present implicitly in the non-bonded interaction potentials between the beads [25].…”
mentioning
confidence: 99%
“…Key examples are multi-component lipid mixtures that model the plasma membrane (Flinner and Schleiff, 2015;Ingólfsson et al, 2014b;Koldsø and Sansom, 2015;Koldsø et al, 2014;van Eerden et al, 2015) and the dynamic model of an entire virion membrane (Reddy et al, 2015).…”
Section: Coarse-grain Resolutionmentioning
confidence: 99%